Physiologically‐based pharmacokinetic modeling of renally excreted antiretroviral drugs in pregnant women. (22nd July 2015) - De Sousa Mendes, Maïlys; Hirt, Deborah; Urien, Saik; Valade, Elodie; Bouazza, Naïm; Foissac, Frantz; Blanche, Stephane; Treluyer, Jean‐Marc; Benaboud, Sihem
Abstract : Aim: Physiological changes during pregnancy can affect drug disposition. Anticipating these changes will help to maximize drug efficacy and safety in pregnant women. Our objective was to determine if physiologically‐based pharmacokinetics (PBPK) can accurately predict changes in the disposition of renally excreted antiretroviral drugs during pregnancy. Methods: Whole body PBPK models were developed for three renally excreted antiretroviral drugs, tenofovir (TFV), emtricitabine (FTC) and lamivudine (3TC). To assess the impact of pregnancy on PK, time‐varying pregnancy‐related physiological parameters available within the p‐PBPK Simcyp® software package were used. Renal clearance during pregnancy followed glomerular filtration changes with or without alterations in secretion. PK profiles were simulated and compared with observed data, i.e. area under the curves (AUC), peak plasma concentrations ( C max ) and oral clearances (CL/ F ). Results: PBPK models successfully predicted TFV, FTC and 3TC disposition for non‐pregnant and pregnant populations. Both renal secretion and filtration changed during pregnancy. Changes in renal clearance secretion were related to changes in renal plasma flow. The maximum clearance increases were approximately 30% (TFV 33%, FTC 31%, 3TC 29%). Conclusions: Pregnancy PBPK models are useful tools to quantify a priori the drug exposure changes during pregnancy for renally excreted drugs. These models can be applied to evaluate alternative dosing regimens to optimize drug therapy during pregnancy.